Refletindo sobre a ausência : sub-representação de mulheres negras no parlamento brasileiro - Nogueira, Maria Janilma Pereira (2023)
Politics as it is understood is a domain occupied predominantly by males, specifically by heterosexual men of white descent. When attention is focused on women in the political context, the discussion of underrepresentation emerges. However, as we deepen the debate and incorporate the perspective of black women, the theme expands beyond of mere under-representation, encompassing a critique of established political paradigms and presenting a political antithesis to which society is accustomed. Given the context presented, this paper addresses the underrepresentation of black women in Brazilian politics with a focus on the intersectionality of gender and race. One argument used is that it is the left-wing parties that, most of the time, enable the entry of black women into the political field. And that gender and racial violence, commonly observed in the political space, has become a significant obstacle to the participation of these women. The locus of the research is social networks (twitter), that is, cyberspace. In this context, three women were selected as interlocutors: Andréa de Jesus (PT), Benedita da Silva (PT) and Talíria Petrone (PSOL). Jô Oliveira (PCdoB) she is also part of the research as an interlocutor and was the only one to be interviewed. Thus, this work is anchored in the qualitative methodology, having the interview script and netnography as fundamental tools of data analysis. In this process of analysis, comments from of people who interacted with the posts published by the interlocutors on their social network Twitter, looking for manifestations of gender and racial political violence. These data make up the first part of the research, and the second part is organized based on the discourse of Jô Oliveira, regimented by the interview. The arguments of authors such as: Almeida (2019), Davis (1981), Collins (2019), Carneiro (undated), Gonzalez (2020), Hooks (2018) Kilomba (2019), serve as a theoretical framework, Recuero (2009), Campos (undated), among others who reflect on black women, Black feminism, political participation, political representation, social networks, black women in politics and, consequently, a public sphere that perceives black women as subjects capable of changing the order. Considering that the path to political parity is far from being achieved, it is crucial to discuss the need for a huge portion of the population that needs to be properly inserted into all social spheres. Because they intersect gender and racial oppressions, black women are the target of increasingly violent episodes. The political field is hostile to these women and social networks become a minefield where countless forms of gender and racial political violence are manifested. Unfortunately, all these hostilities against black women result in fear and impact on mental health, some even give up on institutional politics, and those who resist face considerable effort, because it is not easy to deal with threats and namecalling all the time.